CRISPR/Cas9 from bench to bedside: what clinicians need to know before application? - Li, Zi-Qing; Li, Chao-Hong (Military medical research, 2020)
In October 2020, Dr. Emmanuelle Charpentier and Dr. Jennifer Doudna won the Nobel Prize in Chemistry for their pioneering work in precise genome editing using the CRISPR technology. Although CRISPR technology has developed rapidly in the last decade, there are still many uncertainties before eventual use in clinical settings. In this mini review, we summarize the current efforts in addressing the limitations of CRISPR technology and future directions.